Estrés y su influencia en la conducta social de un adolescente en confinamiento por covid-19 - Garcia Candelario, Mauro Cristopher (2020)
In the development of the case study, the problem of how stress influences the social behavior of an Adolescent in confinement by Covid-19 was presented, presenting itself as a case of current social problems due to the pandemic that is going through the country and the world , focusing on the case of a young man who presents behavioral problems inside and outside his home, in addition to poor academic performance, also presents somatic symptoms and problems falling asleep from the beginning of his quarantine. By collecting information in the clinical interview and the psychometric tests applied, a diagnosis was obtained, in addition to observing other factors that are relevant to the patient's intervention process. In contrast to the results obtained, a therapeutic planning based on the cognitive-behavioral model could be carried out, which will help us to be able to modify certain cognitive distortions and in turn improve the patient's behavior.